A percepção de gestores e professores de uma universidade privada confessional sobre a participação do corpo docente na gestão das mudanças - Santos, Genira Rosa dos (2014)
This study was developed with the intention of investigating how managers and teachers perceive the participation of faculty in managing changes in a private confessional university, during the years 1990-2013, which resulted in the construction of a management model. Managers and teachers that lived through the experience are called collaborators, the living documents of this research, giving voice to the history of this higher education institution, according to modern oral history used as a methodological tool, as conceived by Meihy (2006 and 2011). This theme emerged from discussions on issues of evaluation in education, reflecting on the allocation of the results obtained in institutional evaluation. We raised the possibility of using diagnoses made in assessments to promote improvements in educational institutions with the participation of teachers in managing change. We hypothesized applicability to the educational field of change management models derived from the science of management, which are widely adopted in management practices of business organizations. The theoretical concepts of educational researchers who attribute failure in reforming to the difficulties of dialogue between cultures that coexist in the school environment contributed to substantiate the theme: Escolano (2005), Perez Gomes (2001), Goodson (2008) and Canário (1996). What should be the final conclusions are just reflections on new hypotheses, hence it is a present time story and that ""will remain being told, anywhere wherever there are people.""